Nordic walking as alternative physical activity for population with neuropathy on foot - P. Pérez; S. Llana; A. Encarnación; M. A. Fuster (Asociación Española de Ciencias del Deporte, 2010)
During last decade, Nordic Walking (NW) is more and more being practiced by the population. The benefits associated to NW are several, nevertheless, does not know their effect on plantar pressure. The objective on this study it emphasizes the analysis on the plantar pressure depend on speed and experience on NW vs gait. By means of a Pedobarography system, plantar pressures in 9 zones on foot were registered on 2 speeds (slow/fast) and two conditions (NW versus gait). The results show as the NW experience owns a smaller pressure at the central-metatarsal zone (~ 50%), and increase at heel zone (~ 23%) and first toe (~ 13%) with respect to the gait. Also, these experts showed lees pressure at metatarsal zone (~ 40%) during gait, and lees plantar pressure in practically all zones, even at increase the speed. Key Words:  gait, plantar pressure, nordic walking, speed.